Simultaneous Jamming-and-Transmitting Scheme for Spectrum-Sharing Relaying Networks with Nonlinear Energy Scavenging. (19th October 2021) - Pham-Minh, Triet; Ho-Van, Khuong; Nghi-Vinh, Khanh
Abstract : This paper recommends a simultaneous jamming-and-transmitting scheme for spectrum-sharing relaying networks with nonlinear energy scavenging. More specifically, spectrum-sharing relaying networks include a secondary source which expects to communicate with a secondary destination but impossible due to communication blockage between them, a secondary relay which helps the source overcome this blockage, a primary receiver, and a wiretapper which steals secret messages from both source and relay. To motivate assistance, the relay scavenges radio frequency energy from the source with practical nonlinear energy scavenger (NL-ES) instead of linear energy scavenger (L-ES) as in previous publications. Additionally, both source and relay perform simultaneous jamming-and-transmitting to secure their communication. The intercept and outage probabilities of the recommended scheme are evaluated through exact closed-form formulas, which are corroborated by Monte-Carlo simulations. Illustrative results show that the proposed scheme offers the reliability-security trade-off yet suffers error floor at large maximum transmit/interference power. Moreover, its performance can be optimally set with appropriate system parameters. Notably, the proposed scheme can guarantee absolute security with proper parameter setting. Furthermore, the NL-ES is practical but performs significantly worse than the L-ES.